Imidacloprido e fipronil em mel de Apis mellifera - Rosa, Karine Medina (2021)
The utilization of agricultural pesticides plays an important role in the quality of the crop and food protection, providing benefits for increasing productivity and reducing pests. However, when they hit beyond the desired target, the consequences are damage caused to ecosystems. The contamination of bees by pesticides occurs during the collection of nectar and pollen through visits to contaminated flowers and airborne particles. For this reason, both the bees and honey, their main product, can be environmental monitoring tools. Bees are in the process of disappearing in various parts of the world, which results in the menace of food security. Therefore, it was established as the objective of this thesis the extraction and quantification of pesticides Imidacloprid and Fipronil in organic and conventional honeys, commercialized in supermarkets and health food shops, as well as the comparison of the results found with the maximum residue limits established by legislation. The honey samples were analyzed in the Laboratory of Agro-Environmental Analyses of the Western Paraná State University (Unioeste), with four of the samples being organic honey and the other four, conventional honey. Extraction was achieved by using SPE C18 cartridges in a minifold. Analyte elution was performed in TurboVap® LV. Analytes were resuspended in methanol and transferred to chromatography vials. The determination of imidacloprid was by HPLC and fipronil by CG-ECD. In order to attest the reliability of the method, some validation parameters were investigated: selectivity, linearity, detection limits, quantification and recovery limits. The results found in the validation parameters were satisfactory. Three samples were contaminated by imidacloprid, two of them being organic honey and one, conventional honey, with concentrations ranging from 0.45 µg ml-1to 4.55 µg ml-1, whereas fipronil was detected in seven of the eight samples, three of which were organic honey and four of conventional honey, with concentrations ranging from 0.04 µg ml-1 to 0.14 µg ml-1, all above the LMRs determined by FAO and EU. Organic honey showed greater contamination than the conventional one. For this reason, it is suggested that more research aimed at the analysis of organic foods be implemented, in order to ensure more safety for consumers who purchase these products. Ultimately, it is recommended that the authorities work to raise awareness among farmers, warning them about the disappearance of bees around the world and their importance for agricultural activity, as well as to provide guidance on the need for common sense when applying pesticides.